Identifikasi Tingkat Berpikir Geometri Mahasiswa Calon Guru Sekolah Dasar Berdasarkan Teori Van Hiele - Wulida Arina Najwa (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2022)
Geometry is one of the main materials for learning mathematics in elementary schools. So that students as prospective elementary school teachers should have mastered the concept of geometry. In addition, prospective elementary school teacher students should also know the level of students' geometric thinking. The goal, before the teacher knows the level of thinking of students, he should know the level of geometric thinking he has. The reference used in looking at the geometric thinking level is the Van Hiele thinking level. This study aims to identify the leveling of the geometric thinking stage of elementary school teacher students using the Van Hiele thinking level. The method used in this research is descriptive quantitative research. A written test questionnaire from the Van Hiele Geometry Test (VHGT) was used as an instrument in this study. The results showed that the geometric thinking level of prospective elementary school teacher students only reached level 1 or the introduction level.